2015
DOI: 10.1111/pbr.12316
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic QTL mapping for plant height in Upland cotton (Gossypium hirsutum)

Abstract: Plant height served as one of model traits to analyse dynamic development. The objective of this research was to investigate quantitative trait loci (QTL) and dynamic QTL for plant height trait using an intraspecific recombinant inbred line (RIL) population and a constructed genetic map in Upland cotton (Gossypium hirsutum L.). Totally, 41 QTL and 23 conditional QTL controlling plant height were detected at two experimental environments, respectively. Four stable QTL were identified simultaneously in both envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 55 publications
3
35
0
Order By: Relevance
“…, , Shang et al. ,c, ; hereinafter referred to as ‘XZ hybrid’), derived from a cross of ‘GX1135’ and ‘GX100‐2’. The other one has common female parent with ‘Xinza 1’, derived from the cross between ‘GX1135’ and ‘VGX100‐2’ (hereinafter referred to as ‘XZV hybrid’).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, , Shang et al. ,c, ; hereinafter referred to as ‘XZ hybrid’), derived from a cross of ‘GX1135’ and ‘GX100‐2’. The other one has common female parent with ‘Xinza 1’, derived from the cross between ‘GX1135’ and ‘VGX100‐2’ (hereinafter referred to as ‘XZV hybrid’).…”
Section: Methodsmentioning
confidence: 99%
“…It was bred by the Cotton Research Institute of Dezhou (Shandong Province, China) and Biotechnology Research Institute, Chinese Academy of Agricultural Sciences, and released as a cultivar in Shandong Province as well as in Yellow River Region, China, in 2007 (Shang et al. ). The F 1 hybrid ‘Ezamian 10’ was used as control CK 2 at Xiangyang (E3).…”
Section: Methodsmentioning
confidence: 99%
“…Agronomic traits, especially plant morphological attributes such as PH, FBN, height of the node of first fruiting branch, and angle between stem and fruiting branch, play a decisive role in the architectural construction of crops, which impact agricultural practices, including reasonable increases in planting density and mechanical managements of crops (Mei et al 2016;Shang et al 2016). Among them, PH and FBN are important plant morphological attributes, which have a certain impact on the formation of yield (Ge et al 2012;Hussain et al 2000;Li et al 2010;Tang et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…PH is an important component of ideal plant architecture and plays an important role in cotton breeding (Jiao et al 2010;Ma et al 2019b;Miura et al 2010;Wang et al 2018). Studies demonstrated that PH and FBN had important effects on cotton yield and mechanical harvesting (Su et al 2018;Ma et al 2019b), but it is still necessary for researchers to understand the genetic basis of PH and FBN and how they impact plant architecture (Qi et al 2017;Shang et al 2016;Song and Zhang 2009;Wang et al 2006;Zhang et al 2006). Therefore, further study on these agronomic traits will be of great significance for cotton plant-type breeding and the application and distribution of mechanical harvesting technologies in cotton production.…”
Section: Introductionmentioning
confidence: 99%
“…More genetic information can be obtained by analysing the expression effect of related genes/QTL during development stages than developmental endpoints alone (Peng et al, 2003; Wurschum et al, 2015). Multiple major QTL and simultaneous expressed QTL at different stages were found on the dynamic QTL mapping for PH of wheat, cotton and rice, which revealed that PH had different temporal and spatial expression patterns at different stages (Liu et al, 2010; Shang et al, 2015; Venuprasad et al, 2012; Wu, Wang, Chang, & Jing, 2010; Zhang et al, 2017; Miedaner et al 2018). These studies indicate that the quantitative traits were expressed differently at different stages.…”
Section: Introductionmentioning
confidence: 99%